RATIONAL SUFISM: The Influence of Harun Nasution’s Thought in the Academic World in Indonesia - Khaidir, Piet Hizbullah; Riyadi, Abdul Kadir; idri, Idri; Ibrahim, Azhar; Fathurrofiq, Fathurrofiq (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Sufism is a spiritual exercise dimension often carried out irrationally. Meanwhile, rationalism is a faculty of mind based on rational dimension, thus, it is almost impossible to elaborate both. Harun Nasution’s thought blended them to be the Indonesian Muslims’ way of thinking and live his life both spiritually and ascetically. His rational Islamic thought influenced the Indonesian thinkers profoundly until today. Analyzing his thought, this paper explores the data about him using Edmunds Husserl’s Phenomenology Theory. The phenomenological historical approach aims at understanding the text about Harun Nasution and his thought from the way the text says about it. In other words, this paper attempts to apprehend his rational sufism based on his works, namely Islam Rasional and Mistisisme dalam Islam. His intentional consciousness with regard to his Islamic rationalism blended with sufism is a factor in accordance with the trend within Indonesia’s intellectuals’ Islamic thought. It particularly influenced his students in the academic and activist world. As a study reflection on his thought and the intellectual influence academically, Islam should be presented as a historical religion that is expected to answer and explore real problems in the society. Islam should be studied with a holistic, multidisciplinary, and interdisciplinary approach.